Theatre as a Medium for Children and Young People: Images and Observations - Schonmann, Shifra (Landscapes: the Arts, Aesthetics, and Education,, 2006)
This book is a journey into the dual territory of educational and theatrical settings. It advances the knowledge in these settings by touching upon provocative questions, by dealing with the limitations and challenging the new possibilities of theatre for young people. It is an attempt to bring intellectual rigour and some theoretical perspectives drawn from recent theatre and aesthetic theory to the field of theatre for young people. It fills the gap in the literature on theatre for young audiences. The author poses questions of the work that are penetrating and thought provoking and clearly stem from her own observations of and reflections upon various kinds of children's theatre (CT) and of 'watching children watching' CT over many years. This book is an analysis of images and arguments in theatre for young people. It aims at triggering the reader's interest in this subject as an artistic, educational and cultural phenomenon.